Association between chronic hepatitis C virus infection and low muscle mass in U.S. adults - Gowda, Charitha (J Viral Hepat, 2014)
Given that low muscle mass can lead to worse health outcomes in patients with chronic infections, we assessed if chronic HCV infection was associated with low muscle mass among U.S. adults. We performed a cross-sectional study of the National Health Examination and Nutrition Study (1999-2010). Chronic HCV-infected patients had detectable HCV RNA. Low muscle mass was defined as <10(th) percentile for mid-upper arm circumference (MUAC). Multivariable logistic regression was used to determine adjusted odds ratios (aORs) with 95% confidence intervals (CIs) of low muscle mass associated with chronic HCV. Among 18,513 adults, chronic HCV-infected patients (n=303) had a higher prevalence of low muscle mass than uninfected persons (13.8% versus 6.7%; aOR, 2.22; 95% CI, 1.39-3.56), and this association remained when analyses were repeated among persons without significant liver fibrosis (aOR, 2.12; 95% CI, 1.30-3.47). This study demonstrates that chronic HCV infection is associated with low muscle mass, as assessed by MUAC measurements, even in the absence of advanced liver disease.